PENGARUH KOMITMEN ORGANISASI DAN PENGETAHUAN MANAJER TERHADAP KEBERHASILAN PENERAPAN SISTEM INFORMASI AKUNTANSI - Fadhilah, Brilianti Nurul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
TheÂ  purposeÂ  ofÂ  thisÂ  researchÂ  isÂ  toÂ  examineÂ  theÂ  influenceÂ  ofÂ  organizationÂ  commitmentÂ  andÂ  theÂ  managerâs knowledgeÂ  toÂ  theÂ  successfulnessÂ  ofÂ  theÂ  implementationÂ  ofÂ  accountingÂ  informationÂ  systemÂ  atÂ  HajiÂ  General Hospital of Surabaya. Based on the result of calculation it is obtained that the R2 determination coeffecient value (R Square) is 0.953 which shows that organization commitment and the managerâs knowledge can explain the ImplementationÂ  ofÂ  AccountingÂ  InformationÂ  SystemÂ  isÂ  approximatelyÂ  95.3%Â  whileÂ  theÂ  remainingÂ  4.7%Â  is explained by other variable outside the research. The organization commitment and the managerâs knowledge simultaneouslyÂ  andÂ  partiallyÂ  hasÂ  anÂ  influenceÂ  toÂ  theÂ  successfulnessÂ  ofÂ  theÂ  implementationÂ  ofÂ  accounting information system at Haji General Hospital of Surabaya. Â Keywords:Â  OrganizationÂ  Commitment,Â  ManagerâsÂ  KnowledgeÂ  andÂ  theÂ  ImplementationÂ  ofÂ  Accounting Information System